Implementasi Paradigma Integrasi Keilmuan dalam Pendidikan Islam - Emi Mustaqimah; Suyadi Suyadi (JIE (Journal of Islamic Education), 2023)
Islamic education is a study that is very relevant in every era. The reasons are, First, educators always involve humans as objects that are always dynamic. Second, there is a need for new innovations in education. Third, globalization demands that education must be open, follow the era, and be IT-based. Dynamic demands, innovation and creativity are challenges for the world of education. The Islamic Education System, which has been the guideline for the last period, actually still uses the Classical Education system. Educational reform by integrating Islamic education and neuroscience is the hope for the better. The effort is to reconstruct Islamic education according to its nature. The purpose of this study is to explain that Islamic education is starting to improve itself to restore the glory of previous educational developments, by reconstructing it by combining classical education and contemporary education by integrating neuroscience as a new foothold. This research is an interdisciplinary and qualitative research, namely library research. Sources of research data were referred to from literature in the field of Islamic education and neuroscience which were analyzed by content analysis. The results of the study show that hybridization in strategies and materials that are integrated into the use of neuroscience will produce a new learning that is easier for students to understand.